Security Analysis : Principles and Technique - Klarman, Seth A.; Grant, James; Greenwald, Bruce; Lowenstein, Roger (Chennai : Mc Graw Hill Education, 2017)
Presents David Dodd and Benjamin Graham's original 1934 guide to value investing, with strategies and advice that are still relevant in the twenty-first century, with additional commentary from contemporary investment professionals
Keywords: Securities -- United States; Investment analysis; Speculation